Political and literary commitment through the lens of modern age: Aimé Césaire and today - Iruka, Ebelechukwu Eucharia (Eddissi Languages Journal, 2026)
Aimé Césaire, co-founder of negritude, devoted his life to the liberation of his people. His commitment, rooted in a neo-Marxist perspective, aimed to emancipate oppressed peoples, particularly the objectified black population. His concept of negritude was a revolt against the devaluation of black culture and an affirmation of African identity. This article, titled Political and Literary Commitment Through the Lens of Modern Times: Aimé Césaire and Today, examines the extent of his influence, both past and present, and explores how his ideas continue to inspire liberation movements and struggles against oppression. His commitment, rooted in a neo-Marxist perspective, aimed to emancipate oppressed peoples, particularly the objectified black population. His concept of negritude was a revolt against the devaluation of black culture and an affirmation of African identity. By revisiting his career, the article highlights the relevance of his thinking in understanding contemporary challenges and struggles for equality and social justice. Today, although some consider negritude outdated, it remains a founding moment of black consciousness and continues to inspire struggles for equality and recognition. Negritude is a phenomenon that has marked human history, and this history can never be erased because it is valid.